2020
DOI: 10.1002/cjoc.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Interesting Diarymethane Derivatives from Securidaca inappendiculata

Abstract: Summary of main observation and conclusionSecurines A—E, three dimeric diarymethane derivatives (1—3) and two enantiomeric diarymethane derivative monomers (4 and 5), were isolated and characterized from the medicinal plant Securidaca inappendiculata. Compounds 1 and 2 are a pair of enantiomeric diarymethane derivative dimers, and compound 3 is a mesomeric diarymethane derivative dimer. Their structures were determined by a combination of spectroscopic data, X‐ray crystallography, electronic circular dichroism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…alpine by us. As our continuing efforts to explore new antiplasmodial agents from natural products, [ 27‐29 ] compounds 8 , 10 , and 11 were selectively tested for antimalaria activity against Plasmodium falciparum strain Dd2 (resistant to chloroquine, pyrimethamine, and mefloquine) using an SYBR‐Green I assay, [ 30‐31 ] with artemisinin as the positive control (IC 50 = 13 ± 0.9 nmol/L). Compounds 10 and 11 exhibited moderate inhibitory effects with IC 50 values of 3.9 ± 0.9 and 10.3 ± 1.8 μmol/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…alpine by us. As our continuing efforts to explore new antiplasmodial agents from natural products, [ 27‐29 ] compounds 8 , 10 , and 11 were selectively tested for antimalaria activity against Plasmodium falciparum strain Dd2 (resistant to chloroquine, pyrimethamine, and mefloquine) using an SYBR‐Green I assay, [ 30‐31 ] with artemisinin as the positive control (IC 50 = 13 ± 0.9 nmol/L). Compounds 10 and 11 exhibited moderate inhibitory effects with IC 50 values of 3.9 ± 0.9 and 10.3 ± 1.8 μmol/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antiplasmodial activity was measured using an SYBR‐ Green I assay against Plasmodium falciparum strain Dd2 with artemisinin as the positive control according to the previously reported method. [ 30‐31 ]…”
Section: Methodsmentioning
confidence: 99%
“…Extraction and isolation procedures were carried out according to previously reported methods [26–30] . Specifically, the air‐dried and powdered whole plants of S. wightianus (3 kg) were soaked with 95 % EtOH (20 L×3) to give a residue (350 g), which was suspended in warm water followed by extraction with EtOAc.…”
Section: Methodsmentioning
confidence: 99%
“…alpina. 8 With our continuing efforts to explore new antiplasmodial agents from natural products, 5,[24][25][26][27][28] all the compounds were tested for antimalarial activity against the Plasmodium falciparum strain Dd2 (resistant to chloroquine, pyrimethamine, and mefloquine) using an SYBR-Green I assay, with artemisinin as the positive control. The results (Table 8) showed that no compound exhibited more than 41% inhibition at 1 μM.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%